The Effect Of Economic Development On The Fulfillment Of The Right To A Good And Healthy Environment In South Kalimantan Province - Nurul Listiyani; Rizka Zulfikar; Muhammad Erfa Redhani (CV. Inara, 2021)
The right to a good and healthy environment is a human right guaranteed by the 1945 Constitution. Human rights in the field of the environment are very important, therefore the government should be present in ensuring that citizens get a good and healthy environment. The fulfillment of the right to a good and healthy environment is strongly influenced by variables outside the law such as economic variables, poverty, unemployment, and the Human Development Index (HDI).Because of that, This study aims was to exploring the relationship of sectoaral regional income (SRI), poverty, unemployment and Human Development Index (HDI) in spesific region to the environment quality. Indicators used in this research are SRI of the industrial sector, mining sector, agricultural/plantation /forestry/fishery/livestock sectors, poverty, unemployment and HDI. The type data used is secondary data from the Department of Environment, the Department of Energy and Mineral Resources, and also the Central Bureau of Statistics of South Kalimantan Province for the period 2006 – 2020.Because of that, This research using secondary data from Central Bureau of Statistics for period 2006 – 2020. The method used in this study is descriptive quantitative using structural equation model. Our results from this study were (1) SRI of the industrial sector, mining sector, agricultural/plantation /forestry/fishery/livestock sectors, poverty, and human development index (HDI) were give significant effect to environment quality because all value of CR ≥ 1.96 and probability < 0.05 (2) The unemployment indicator was not give a significant effect to environment quality because from the effect test, the value of CR ≥ 1.96 and probability < 0.05.